Kasr Al-Ainy's psoriasis unit protocol for the management of psoriasis, part I: topical and systemic therapies - Hoda Rasheed; Hesham A.Z El-Moaty; Mohamed H.M El-Komy; Heba Mashaly; Khadiga S Sayed; Vanessa Hafez; Marwa S El-Mesidy; Eman R Said; Marwa A Amer; Aya M AlOrbani; Dina G Saadi; Mona El-Kalioby; et al. (Wolters Kluwer Medknow Publications, 2019)
Psoriasis is a chronic multisystem inflammatory disease affecting primarily the skin and joints and also involves several comorbidities. The disease affects between 0.2 and 4% of the population worldwide. The approach to the patient and its proper management needs a holistic approach, where the physician treats the patient and not just the plaques of psoriasis. The Kasr Al-Ainy Psoriasis Unit developed a protocol of therapy for psoriasis, based on the best available scientific evidence and the expert opinion of the team, taking into consideration the regional characteristics of our patients (factors such as cultural, socioeconomic, and epidemiologic specificities). The protocol offers an algorithm for the choice of adequate therapy for patients with psoriasis, both for initiation and for maintenance, according to the severity and the course of the disease. Topical and systemic therapies available in the Egyptian market are highlighted for their efficacy and safety data. An algorithm for screening of cardiovascular comorbidities is also presented. This protocol is the backbone of our daily practice in Kasr Al-Ainy Psoriasis Unit and we beleive physicians dealing with psoriasis in primary-care centers or in their clinics can find it useful to deliver a better service to their patients.